Indeks Pariwisata Halal (Implementasi Fatwa DSN MUI Tentang Pedoman Penyelenggaraan Pariwisata berdasarkan Prinsip Syariah di Kota Bukittinggi) - Muhammad Ghafur Wibowo (Universitas Alma Ata, 2020)
The halal tourism industry is increasingly developing in Indonesia, which is marked by government support and also the response of tourism industry players. In order to provide a quality standard of service for Muslim tourists, a halal tourism index has been created globally and nationally. This study tries to measure the Halal Tourism Index (HTI) with a different basis and method than the existing ones. Referring to the Fatwa of DSN MUI concerning Guidelines for Implementation of Tourism Based on Sharia Principles, this study calculates the HTI in Bukittinggi City. The results showed that the HTI in Bukittinggi City has met the good criteria, even though it does not have halal tourism regulations yet. Aspects that are still lacking in terms of managing halal tourism in Bukittinggi City are halal product certification and collaboration with Islamic financial institutions.